Pharmaceutical industry use of key opinion leaders to market prescription opioids: A review of internal industry documents - Brian Gac; Kgosi Tavares; Hanna Yakubi; Hannah Khan; Dorie E. Apollonio; Eric Crosbie (Exploratory Research in Clinical and Social Pharmacy)
Objective: Prescription opioid-related deaths increased by 200 % from 2000 to 2014. There has been limited research regarding channels used by pharmaceutical companies to market prescription opioids. In this study, we investigated pharmaceutical industry use of key opinion leaders (KOLs). Methods: We conducted a retrospective qualitative review of the first 503 opioid industry documents publicly released, which are held at the University of California, San Francisco Opioid Industry Document Archive (OIDA). We reviewed documents including legal rulings, correspondences, witness statements, clinical studies, and corporate communications for relevance and coded them by themes. Results: Between 2001 and 2019, pharmaceutical companies including Janssen, Purdue Pharma, and Cephalon identified, recruited and developed individuals they referred to as “Key Opinion Leaders,” (KOLs) that they recognized could reach strategic audiences to influence prescriber behaviors. Pharmaceutical companies identified KOLs through a variety of sources ranging from partnerships with PR firms to social media analysis and congressional and regulatory sources. Companies recruited KOLs through various methods including surveys to identify common names identified by physicians, internal rankings based on friendliness, and opioid prescribing behaviors. Companies employed KOLs as speakers at conferences for branded opioid products, authors of research articles in support of prescription opioids, and consultants regarding marketing strategies. Conclusions: KOLs were employed by the pharmaceutical industry to leverage their reputations in the service of encouraging healthcare providers to prescribe more opioids. It is critical to ensure that researchers and leaders in the medical field are aware and critical of pharmaceutical corporate profit-led biases and are free from conflicts of interest to avoid inappropriate prescribing and minimize adverse outcomes for patients.